¿Son convincentes los argumentos de Epicuro y Lucrecio para rechazar el temor a la muerte? - Rosell, Sergi (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2022)
The present paper attempts to reconstruct and assess the main Epicurean arguments against the idea that death is an evil for the one who dies.In order to fight against the life anguished by the fear of death, Epicurus and Lucretius deploy a series of arguments aimed at showing the irrationality or thelack of justification of this fear. Although I share the thesis according to which an eudaimonic life entails the acceptance of our mortal nature, I suggest, however, that this does not force us to embrace the much more radical thesis according to which “death is nothing for us”. Particularly, the paper argues that the discussedarguments invalidate the fear of the fact itself of being dead, but not other fears related to the fact of not carrying on living.

Este artículo se ocupa de reconstruir y evaluar los principales argumentos epicúreos contra la idea de que la muerte es un mal para quien muere.Para combatir la vida angustiada por el temor a la muerte, Epicuro y Lucrecio despliegan una serie de razonamientos que aspiran a mostrar la irracionalidado falta de justificación de este temor. Compartiendo la idea de que una vida eudaimónica requiere que asumamos nuestra naturaleza mortal, se defiende, sinembargo, que esto no nos fuerza a aceptar la tesis mucho más radical de que “la muerte no es nada para nosotros”. En particular, se arguye que los argumentosdiscutidos invalidan el temor al hecho mismo de estar muerto, pero no otros temores a no seguir viviendo.
Are Epicurus’ and Lucretius’ Arguments Against the Fear of Death Convincing?
Keywords: Epicureanism; Evil; Hedonism; Sensation; Privation; Epicureísmo; Mal; Hedonismo; Sensación; Privación; https://purl.org/pe-repo/ocde/ford#6.03.01